Regional and National Variations in Reasons for Gluten Avoidance. Issue 8 (September 2018) - Zylberberg, Haley M.; Yates, Shireen; Borsoi, Carla; Green, Peter H.R.; Lebwohl, Benjamin
Abstract : Background: Although studies have assessed the prevalence of celiac disease (CD), less is known about the prevalence of gluten avoidance because of nonceliac gluten sensitivity (GS). The avoidance of foods other than gluten is also understudied in these 2 groups. Methods: Participants visiting a web site for information about a newly developed portable gluten detection device (Nima) were instructed to complete questions about food and gluten avoidance patterns. We assessed the relative proportion of CD and GS across world regions and United States (US) regions and determined the distribution of food avoidance patterns. Results: CD was reported in 6474 respondents and GS in 2597 respondents. Within the United States, the majority of avoiders of gluten reported having CD (69.8%), with the highest ratio of CD to GS in the Northeast (CD: 74.3%; GS: 25.7%) and the lowest in the West (CD: 67.1%; GS: 32.9%) ( P <0.0001). Compared with the United States, all other countries had lower proportions of GS, with the lowest in Argentina (CD: 94.7%; GS: 5.3%; P <0.0001). Food avoidances other than gluten were reported by 25% of respondents, with avoidance in all categories more common in GS than CD ( P <0.0001). Conclusion: There is a significant difference in the relative rates of CD and GS within the United States and worldwide. Food avoidance other than gluten seems to be a more common component of GS than CD. Future research should focus on the causes of these international and US regional differences and the significance of other food avoidances.